PENGARUH ASAL DAERAH DAN JUMLAH AKUN ONLINE SHOP TERHADAP POLA HIDUP KONSUMTIF MAHASISWA - Yulianti Yulianti; Ekawati Dewi; Baiq Rika Ayu Febrilia (Delta: Jurnal Ilmiah Pendidikan Matematika, 2020)
The development of an increasingly modern era, resulting in changes in people's lifestyles that change, so that the consumptive pattern of society is increasing. Thus, researchers conducted a study on this subject which aims to analyze the factors that influence the consumptive lifestyle of students by using ordinal logistic regression analysis. The focus of the factors observed was regional origin and the number of online shop accounts. Data collection was carried out using an online Google survey form sheet from Mandalika University Education students in one faculty of 100 people. The results showed that the influencing factor significantly came from the variable number of online shop accounts